12x-13=12x-13

Simple and best practice solution for 12x-13=12x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-13=12x-13 equation:



12x-13=12x-13
We move all terms to the left:
12x-13-(12x-13)=0
We get rid of parentheses
12x-12x+13-13=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 11-9x=-115 | | 9x-7=9x+16 | | 3x−2=7 | | 9x*x+7*x=4 | | (7/4)x+3/4=(-3x+5)/4 | | x/3+1=2x+3 | | -5-x+3=17 | | 50=1.8c-32 | | X2-39x-106=0 | | -2-x-6=24 | | 6x+8x-5=0 | | x*0.1=60,000 | | x*0.1/100=60,000 | | t+t+t=12 | | 12÷6×2=x | | 5w2=80 | | X=12÷6a | | -6+x-4=16 | | 30k+25=75 | | X=12/6a | | 80+(11x-8)=180 | | 5a-6=2a+3 | | X•2x=40 | | 0.8/x=10 | | (4^x)^x=4*8^x | | 3*(x-6)=2*(-7) | | 4(x+2)-3(2x-2)=18 | | 10.86-0.25x=x | | x+4×x=65 | | 10x+2(7x-2)=3x+5(4X3+) | | 5x+24=12x-60x= | | 2+2x-1/5=5 |

Equations solver categories